WAWASAN YANG MENINGKATKAN: PERKEMBANGAN E-BOOKLET PROGRESIF DALAM SUHU DAN PANAS - Afrida, Juniar; Ramadhan, Muhammad Daffa Syahrul; Alaidin, Samsul Fala (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This study aims to evaluate the feasibility of an E-Booklet centered on temperature and heat materials. Employing the Research and Development (R&D) methodology, the research adheres to the Alessi and Trollip model, progressing through planning, design, and development stages. Validation instruments, encompassing validation sheets for both material and media, were employed. The validation process involved six material experts, including lecturers and teachers, along with three media experts. Results demonstrate the high feasibility of the developed E-Booklet for temperature and heat materials, attaining an average score of 95.58%, categorized as